Critical success factors of small and medium enterprises in (SMEs) : Giyani town, South Africa - Tloubatla, Mpho (My University, 2017)
Background: Small and medium enterprises (SMEs) have in recent years become the main drivers of the economy. They contribute to job creation and enhances the living standards of many nations. However, little is known regarding the critical success factors of SMEs in South Africa. Aim: The aim of this paper was to contribute to an understanding of the critical success factors of SMEs, and how these factors can assist in the survival, growth and sustainability of South African small businesses. If small business entrepreneurs gain a better understanding of what is required to succeed, they will be in a good position to improve their business the performance. Setting: The study took place in Giyani town, South Africa among owners of SMEs who had been successful in running the small businesses for five years and more. Methods: Using a qualitative research design, in-depth, face-to-face interviews were conducted with 12 small business entrepreneurs that owns and run small businesses in Giyani town. The study methodology included sampling procedure, data collection and development of interview questions. Responses were analysed against the study literature, and conclusions were made. Results: The empirical investigation of this study has revealed that there are other critical success factors contributing to the success of SMEs in South Africa, other than those expressed in the literature. The significance of this study is the contribution to knowledge of the critical success factors of SMEs in South Africa. Conclusion: The empirical research finding has revealed some of the critical success factors of SMEs that have been found to be in line with the study literature. Additional critical success factors have been reported by the Giyani small business community to contribute to the success of SMEs, which the study explores in details.
MBA
Keywords: SMEs, Critical Success Factors, Giyani town